Katutubo glimpses of Philippine indigenous culture. ([Makati City?] Filipinas Heritage Library Ayala Foundation, 2000)
Katutubo: glimpses of Philippine Indigenous culture takes you to four indigenous communities in four different destinations across the country: up north in the province of Abra are the Tinguian, east to the Pacific side of the archipelago are the Agta of Isabela, down South Cotabato are the T'boli of Lake Sebu, and on the Island of Mindoro, the Hanunuo-Mangyan. This multimedia CD-ROM allows you to learn about some of our old traditions from the people who have kept them alive, and to experience a bit of their culture: their art, politics, livelihood and their belief system; their music, their language. It is an experience of travel and study, in sound and scenery.
System requirements: Pentium powered PC; 16 MB RAM ; WIN NT, 95 or higher ; 640x480 resolutioon and 256 color display ; SGVA Monitor ; soundblaster compatible soundcard ; 4X multimedia CD-ROM drive ; Microsoft mouse or equivalent.